Aspects Relating to the Influence of Climate Conditions and Mineral Fertilisation on Maize Yield - Alin Popa; Adrian Ceclan; Alina Simon; Marius Bardas; Felicia Chetan; Florin Russu (Journal of Agriculture and Rural Development Studies, 2024)
Monitoring climate conditions reveals changes such as the increase in annual average temperatures and the uneven distribution of rainfall. Therefore, focusing on new technological solutions or improvements to existing ones is essential, ultimately resulting in enhanced quantitative and qualitative yields. This study examines the influence of nitrogen and phosphorus fertilization applied according to the current water reserves at different soil depths under the climatic conditions at the Agricultural Research and Development Station in Turda during the studied years. In the three experimental years, two doses of N were applied, namely N-100 kg/ha and N-200 kg/ha using the same dose of phosphorus 40 kg/ha, respectively, phosphorus fertilization was applied in the autumn before plowing to be incorporated into the soil, and the nitrogen dose was applied at the same time as sowing. Climate conditions remain an important factor in crop determination, which is apparent from the data presented in Table 1 where 2023 recorded the best conditions for maize crop development compared to the other years studied, with a yield increase of over 1000 kg/ha, with very significant positive differences, compared to the average of the experimental years. In 2022 and 2024, close quantitative yields are recorded, but with negative differences of up to 750 kg/ha compared to the year's average, in 2022.